Self-Transcendent Emotions and Their Social Effects: Awe, Elevation and Kama Muta Promote a Human Identification and Motivations to Help Others - Pizarro, José J.; Basabe, Nekane; Fernández, Itziar; Carrera, Pilar; Apodaca, Pedro; Man Ging, Carlos I.; Cusi, Olaia; Páez, Darío (Frontiers in Psychology, 2021)
Abundant literature shows the effects of negative emotions on motivations to engage in collective action, and the particular role of shared identities. Here, with a focus on positive affect, we review studies on Self-Transcendent Emotions (STEs) and examine their influence in a) strengthening of a global identification, b) increasing willingness to collectively help others, and c) people’s wellbeing. For this reason, we conducted a review of k = 65 independent studies on the effects of STEs on connection to others and conducted a video-based study. In it, 1064 university students from 3 different cultural regions (Spain and Ecuador) were randomized to answer one of three STE scales (Awe Scale, Elevation Scale, and Kama Muta Scale), and evaluate three videos in random order (prototypical for each STE). Then, they answered a measure of superordinate identity and their willingness to collectively help others (after each video) and self-transcendent values, and wellbeing (at the end). Results from SEM analyses show these STEs motivated a fusion of identity with all humanity, as well as collective intentions to help others, even controlling for individuals’ value orientations. While there are differences among them, these three emotions share common elements and their effects are constant across the different cultural regions. It is concluded that Awe, Elevation, and Kama Muta, even individually experienced, have a significant potential on people’s social life. In particular, in the creation and maintenance of collective action.